Does leverage level matter for return anomaly during rights issue announcements?: the case of Islamic countries - Isiker, Murat (Islamic economic studies, 2021)
Purpose This paper aims to measure investors' perception of the rights issue announcement of publicly listed companies in five stock markets of Islamic countries. Then, these firms are grouped according to their debt level to examine whether abnormal returns are different from those that are highly leveraged. Moreover, Sharīʿah compatibility of firms is checked to understand if return anomaly shows different behaviour around rights issue announcement days. Design/methodology/approach The analysis period includes the years 2010-2019, which includes 362 rights issue announcements. The event study methodology is applied to measure the level of impact that is triggered by the rights issue announcements. Hereafter, one-way ANOVA test is performed to identify whether there exists a difference among the sample groups according to their debt level. Findings Findings suggest that rights issue announcements cause −3.90% fall in share prices on average for the whole sample. However, negative abnormal return is found significant only in Egypt and Turkey. Individual regression analysis results suggest that an increase in debt level worsens the return anomaly only in Egypt. This refers that the rights issue announcement is perceived as less favourable for highly leveraged companies compared to others in this country. Finally, Sharīʿah-compliant companies show better performance compared to non-compliant counterparts around the event dates. Originality/value This paper is novel in evaluating market reaction during rights issue announcements in multiple Islamic countries. Also, to the best of the authors' knowledge, this study is the first attempt to compare return behaviour of Sharīʿah-compliant and non-compliant firms around the rights issue announcements.